Diode laser irradiation increases microtensile bond strength of dentin - Rafael Massunari MAENOSONO; Odair BIM JÚNIOR; Marco Antonio Húngaro DUARTE; Regina Guenka PALMA-DIBB; Linda WANG; Sérgio Kiyoshi ISHIKIRIAMA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Laser irradiation after the immediate application of dentin bonding systems (DBSs) and prior to their polymerization has been proposed to increase bond strength. The objective of this study was to evaluate the effect of diode laser irradiation (λ = 970 nm) on simplified DBSs through microtensile bond strength tests. Forty healthy human molars were randomly distributed among four groups (n = 10) according to DBSs used [Adper™ SingleBond 2 (SB) and Adper™ EasyOne (EO)], and the respective groups were irradiated with a diode laser (SB-L and EO-L). After bonding procedures and composite resin build-ups, teeth were stored in deionized water for 7 days and then sectioned to obtain stick-shaped specimens (1.0 mm2). The microtensile test was performed at 0.5 mm/min, yielding bond strength values in MPa, which were evaluated by two-way ANOVA followed by Tukey's test (p < 0.05) for individual comparisons. For both adhesive systems, diode laser irradiation promoted significant increases in bond strength values (SB: 33.49 ± 6.77; SB-L: 43.69 ± 8.15; EO: 19.67 ± 5.86; EO-L: 29.87 ± 6.98). These results suggest that diode laser irradiation is a promising technique for achieving better performance of adhesive systems on dentin.